Antiretroviral Treatment of U.S. Children with Perinatally-Acquired HIV Infection: Temporal Changes in Therapy between 1991 and 2009 and Predictors of Immunologic and Virologic Outcomes - Van Dyke, Russell B. (2011)
BACKGROUND: Advances in therapy have allowed children with perinatal HIV infection in the U.S. to survive into adolescence. We sought to describe the disease status of a large cohort of such children and identify predictors of their current CD4 count and HIV viral load (VL). METHODS: The Pediatric HIV/AIDS Cohort Study AMP Protocol is an ongoing prospective study conducted at 15 sites in the U.S. Between 2007 and 2009, we enrolled a population-based sample of 451 children with perinatal HIV who were 7–16 years of age at entry. RESULTS: The median age of subjects at entry was 12.2 years, 53% were female, 70% were African-American, and 24% Hispanic. Their median entry CD4% was 33% and 78% had a CD4% ≥25%; 68% had a suppressed VL. The more recent birth cohorts (1994–2002) had a significantly higher CD4% over time than the earliest birth cohort (1991–1993). The significant independent predictors of a higher CD4% at entry were a suppressed entry VL, a higher nadir CD4%, and starting antiretroviral therapy (ART) at a younger age. The mean CD4% at entry for children with a nadir CD4% ≥ 25% was 9.5 percentage points higher than for those with a nadir CD4% < 15% (p < 0.001). Independent predictors of a suppressed entry VL were membership in a recent birth cohort, male gender, HAART use at entry and fewer prior ART regimens. CONCLUSION: Most children with perinatal HIV maintain virologic suppression and good CD4 values. Earlier treatment results in better immune outcome.